Quantitative trait loci for upper thermal tolerance in outbred strains of rainbow trout (Oncorhynchus mykiss) - Perry, G.M.L.; Danzmann, R.G.; Ferguson, M.M.; Gibson, John P. (Springer, 2001)
The expression of three putative QTL for upper thermal tolerance (UTT) was examined in two strains of outbred rainbow trout unselected for this trait using simple-sequence repeat (SSR; microsatellite) markers associated with UTT in backcrosses of lines selected on this trait. Two-way diallel lots in the third generation of an outbred pedigree were exposed to an acute thermal challenge. QTL detection was performed separately by each second-generation parent within each diallel lot, incorporating the effects of full sib families and correlated traits. Inheritance of different alleles at the SSR Ssa20.19NUIG from the sire 93-32-1 was strongly associated with the thermal tolerance of his half sib progeny, explaining 7.5% of their phenotypic variance in this trait. A hierarchical linear model incorporating allelic inheritance from all four grandsires of the experimental diallels (in addition to family specific and covariate trait effects) was also used to detect associations between the SSR and thermal tolerance in their third-generation grandprogeny. Ssa20.19NUIG was strongly associated with thermal tolerance in the grandprogeny of the grandsire G0SVM2. The generally stronger marker-trait associations found in male parents may be partially due to reduced chromosomal recombination rates in male salmonids compared to females. These results indicate the effects of a QTL on a fitness-related trait in unselected populations of rainbow trout.